481. QUANTITATIVE ESTIMATION OF GASTRIC CONDUIT PERFUSION TO SELECT ESOPHAGECTOMY PATIENTS AT HIGH RISK OF IMPAIRED PERFUSION. (24th September 2022) - Ishikawa, Yoshitaka; Zhao, Lili; Chang, Andrew; Lin, Jules; Orringer, Mark; Lynch, William; Lagisetty, Kiran; Wakeam, Elliot; Reddy, Rishindra
Abstract: Impaired gastric conduit perfusion is considered the most important factor of anastomotic leaks following esophagectomy. Gastric ischemic preconditioning (GIP) can improve conduit perfusion and may reduce anastomotic leaks; however, it remains unclear which patients could benefit from preconditioning. The aim of this study is to create a paradigm to select patients at high risk of impaired perfusion who may benefit from GIP. Patients undergoing an esophagectomy with gastric conduit reconstruction and indocyanine green fluorescence angiography from July 2015 to December 2021 (Cohort 1), as well as all patients receiving an esophagectomy from 2003 to 2021 (Cohort 2) were reviewed. Analyzed variables for Cohort 1 included patient pre-operative demographics and ingress index (quantitative assessment of blood perfusion). Multiple linear regression model for conduit perfusion was used to select significant preoperative factors and to build a formula to estimate conduit perfusion. The formula was applied to Cohort 2 to estimate the percentage of patients who could receive GIP prior to esophagectomy. 349 patients were in Cohort 1, and 1965 in Cohort 2. There was a significant correlation with older age and low body mass index (BMI) and impaired conduit perfusion. Other factors, such as heart disease, diabetes, and prior chemoradiation did not correlate (Table). Using only two variables "age" and "BMI", we determined how many could have poor conduit perfusion, defined as a low ingress index of <40 (the median value from the Cohort 1). When applying the formula to Cohort 2, we estimated that 26.7% (525) of patients would be at risk for low perfusion and for anastomotic leaks. Using BMI and age, we are able to risk stratify patients who are likely to have low perfusion in their gastric conduits (Figure, higher risk in red). We feel that this group will be the most likely to benefit from pre-esophagectomy gastric ischemic conditioning.